Futile Pleasures : Early Modern Literature and the Limits of Utility - McEleney, Corey (Book collections on Project MUSE., 2017)
"Examines the ambivalent role that pleasure plays in early modern English writers' attempts to defend the utility of literature. Traces how that ambivalence gets replayed in modern critical frameworks as well as debates about the value of the humanities and liberal arts"--